Implementation of a Web-Based Student Candidate Selection System Using the Simple Additive Weighting Algorithm - Akrom (Jurnal Inotera, 2025)
The rapid development of information technology in the era of globalization encourages various sectors to adopt digital technology, including in the field of education. One important aspect that requires the optimization of technology is the selection process for new student candidates. The manual selection method often takes a lot of time, is prone to errors, and lacks transparency and objectivity. Therefore, the implementation of an information technology-based selection system becomes a relevant and urgent solution. This research aims to design and implement a website-based selection system for student candidates using the Simple Additive Weighting (SAW) algorithm at XYZ Junior High School.The SAW algorithm is chosen for its ability to solve multi-criteria decision-making problems in a simple, efficient, and effective manner. This system is designed to process data of prospective students based on a number of predetermined criteria and then calculate the final scores to determine the rankings of prospective students objectively. The system development process includes stages of needs analysis, interface and system design, program implementation, and evaluation of system functionality and performance. The results of the implementation show that this system can accelerate the selection process, improve calculation accuracy, and provide transparency and fairness in decision-making. Additionally, this system can also serve as a reference for other schools that want to adopt similar technology to enhance the efficiency and quality of the new student selection administration process.